Release of Copper / Magnesium Ions from Hydroxyapatite-Based Fiber Scaffolds Hasten Bone Healing and Regeneration - Adil Elrayah; Jie Weng; Dongqin Xiao; Azher S Barrak (Journal of Techniques)
Releasing inorganic ions from Ca/P biomaterials could provide an alternative approach to using growth factors to improve bone healing. Two types of hydroxyapatite HA fiber scaffolds, copper-doped (CuHA) and magnesium-doped (MgHA), were fabricated by using the sol-gel method. Two types of scaffolds were immersed in simulated body fluid SPF (i,e, Phosphate Buffered Saline PBS) for 30 days. The results after immersions indicated the amount of Cu and Mg ions released from scaffolds. A low amount of Mg and Cu ions could improve vascular endothelial growth factor (VEGF) and angiogenesis around bone, thus can hasten bone healing and regeneration.